Differential diagnosis of primary and metastatic ovarian carcinomas - Zakhartseva, L. M.; Manzhura, O. P.; Vashchenko, I. Yu.; Maistrenko, Ye. V.; Kravchuk, O. M.; Shatrova, K. M.; Rudnytska, O. H. (Pathologia, 2023)
Ovarian tumors constitute 3.4 % of the structure of oncological diseases in women worldwide. However, the ovaries are also a common target for metastasis of carcinoma from other organs. Conducting differential diagnosis between primary carcinoma and metastasis is often challenging. The aim of this study is to highlight the issues of morphological and immunohistochemical differential diagnosis of primary ovarian carcinomas and metastases from carcinomas of various organs to the ovaries. Materials and methods. Data analysis of clinical and pathohistological studies of 381 patients. Paraffin sections for pathohistological studies were stained with hematoxylin and eosin using standard methodology. Immunohistochemical studies were conducted in 161 cases using a panel of antibodies: cytokeratins, estrogen receptors, progesterone receptors, CA125, TTF1, Vimentin, CDX2, Villin, Chromogranin A, Synaptophysin, CD56, GATA, p53, Inhibin A, FOXL-2, PAX-8, Ki-67. The specimens were examined and analyzed using the Axioskop 40 microscope (Zeiss) with the AxioCam MRc camera (Zeiss). Results. The article discusses key issues of differential diagnosis of primary and metastatic ovarian carcinomas based on a large clinical and operational material. The application of an adequate panel of immunohistochemical antibodies for verification is considered. The results of the frequency of occurrence of different histological variants of ovarian carcinomas and metastases to the ovaries from carcinomas of other organs are provided based on our own research from 2019 to 2023. The main morphological and immunohistochemical indicators for practical use in the work of a pathologist in the verification of ovarian tumors are presented. An example of forming an antibody panel, taking into account clinical and morphological indicators in a specific clinical case from our own practice, is given. Conclusions. Metastases of carcinomas from other organs to the ovaries constitute half of all cases requiring immunohistochemical investigation based on morphological structure. The most common are metastases from breast and colorectal cancers. However, the diagnosis of metastatic intestinal carcinoma is particularly challenging, as there is usually no clear clinical picture. In the differential diagnosis of primary and metastatic ovarian tumors, a comprehensive approach to analyzing the clinical presentation, microscopic structure of the tumor, and the surrounding tissue plays a significant role. Additionally, the formation of an antibody panel, taking into account these data, is crucial. The article provides a list of antibodies that have demonstrated greater effectiveness in our work.